SPATIAL ANALYSIS OF HUMAN TOXOPLASMOSIS IN GIANYAR REGENCY BALI - Febianingsih, Ni Putu Eka; Febianingsih, Ni Putu Eka; Artama, Wayan Tunas; Indriani, Citra (International Journal of Psychosocial Rehabilitation, 2020)
Toxoplasmosis is a zoonosis of human and warm-blooded animals. This infection is caused by the parasitic protozoan Toxoplasma gondii. This parasite distributed worldwide. Human Toxoplasmosis causes severe congenital abnormalities including hydrocephalus and mental retardation in infants. T. gondii has infected 15-80% of the world population. The seroprevalence of toxoplasmosis in women in Bali was 63.9% with the highest percentage in Gianyar. The present study was designed to know the spatial distribution of human toxoplasmosis. The study was carried out in Gianyar Regency, Bali Province, in 2015. Seroprevalence of human toxoplasmosis was examined by an indirect ELISA method for IgG Anti-T.gondii with a total of 240 sera. Geographical and environmental characteristics are measured with the Global Positioning System (GPS) and hygrometer. The spatial distribution of toxoplasmosis was mapped by using Geographic Information System (GIS). Seroprevalence of human toxoplasmosis in Gianyar District was 56.7%. Data analysis showed that the elevation and distance of the river from the house are related to the incidence of human toxoplasmosis in Gianyar. The spatial distribution of toxoplasmosis was mapped per cluster by using GIS. Different spatial patterns of toxoplasmosis were identified in elevation and watershed. Cluster with a positive percentage is most prevalent in lowland areas (<200mdpl). High seropositive toxoplasmosis in Gianyar Regency. Toxoplasmosis seropositive should receive treatment and health information. Keep in efforts to increase health knowledge about toxoplasmosis and transmission.